析探科技对个体身份的挑战 ：以《按键的手》与《人工智慧纪事》为研究文本 = A thesis on the challenges posed by technology to one’s identity : using the keyboard hand and the chronicle of artificial intelligence as texts for analysis - 姚丽萍 Yeo, Lay Peng (2014)
科技的迅速发展提高了人类的生活水平，却也带来诸多挑战。在科技万能的时代， 人对自身的认同面临前所未见的挑战。本文将以平路的《按键的手》（1986）与《人工智慧纪事》（1989）为例，探讨科技如何挑战或影响人对于个体身份概念的界定， 促使人重新思考对于人性以及两性问题。《按键的手》探寻的是科技与人异化的相互影响。《人工智慧纪事》将性别议题纳入论述，以女机器人这 Cyborg 形象为女性 提供一条科技与身体思辨的思路， 试图唤醒女性自觉意识，反思科技所赋予身体的影响。本文也将探讨相隔三年之作的《按键的手》与《人工智慧纪事》如何反映了 平路在科幻作品中的深度与宽度的深化演展。其核心关怀始终不变，即关注在科技 时代人与女性的生存困境与状态。The rapid development of Science and Technology brings both benefits and challenges to mankind. One of the challenges posed is that to the human identity. The main focus of this thesis will be to discuss how technologies challenge and influence one’s concept of own identity, prompting humans to rethink about human nature and gender issues. These issues will be examined using Ping Lu’s The Keyboard Hand and The Chronicle of Artificial Intelligence as the texts for analysis. The Keyboard Hand narrates the alienation of mankind in the age of technology while The Chronicle of Artificial Intelligence brings in gender issue into discourse. The latter utilizes the Cyborg figure to arouse self-consciousness in female and reflect on the effects technology could have on the body. This dissertation will also examine how the two texts mirror Ping Lu’s growing depth of thinking and wider perspective in her writing. The living condition of mankind and women in the age of technology remains her core concern in both texts.